Two grafitti and two stamps found in Dehesa Cintruénigo III (Tarazona, Zaragoza) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The Dehesa Cintruénigo III (Tarazona, Zaragoza) site is being excavated by the Centro de Estudios Turiasonenses and corresponds to an old winery that includes a tread area on a trullo type lacus, the remains of a manual beam press of heronian typology and a storage space or cella vinaria, along with two more rooms, also for storage, annexed to which is an area possibly dedicated to housing that remains to be investigated. This paper consists of the publication of a Palaeohispanic grafitto on Campanian A pottery, two Celtiberian stamps on storage pottery and a Latin grafitto on a Celtiberian vessel found in this archaeological site.
Keywords: Grafito; Inscribed stamp; Campanian pottery; Winery; Palaeohispanic epigraphy; Latin epigraphy; Instrumenta inscripta